PENCEGAHAN KEKERASAN TAWURAN PELAJAR/REMAJA DI KELURAHAN BAGAN DELI KECAMATAN MEDAN BELAWAN - Kusbianto Kusbianto; Ariman Sitompul; Syariful Azmi; Rilawadi Sahputra; Ruslan Ruslan; Melky Suheri Simamora; Rina Melati Sitompul; Ahmad Ridho Arif; Edi Setiawan Sipayung (Devote: Jurnal Pengabdian Masyarakat Global, 2025)
Community service in bagan deli district is a district located in the city of medan which is a distance of 22.5 km for 32 minutes from Dharmawangsa University. Community service is a follow - up between the cooperation that has been done between the University of Dharmawangsa with KPPI in medan belawan district office. This activity was carried out by socializing the law with the theme “Prevention of teenage brawl violence in Bagan Deli Village”. This theme is a very important issue to be conveyed and known so that the public knows the legal consequences of violence among adolescents. The service team carried out this service as a form of concern for the people of bagan deli village by discussing the theme of Service and the service team did not provide restrictions to participants to provide questions with problems of preventing teenage brawls. This service was held on October 22, 2025 by meeting directly with the participants by conducting stages, namely preparation, implementation, and results. The results of the implementation of these activities were evaluated by the pengabdi team on community knowledge about brawl prevention after the pengabdi team socialized so that the information submitted to the community could be accepted as a whole.